Lineage-Specific Functionality of an Interferon Regulatory Factor 5 Lupus Risk Haplotype: Lack of B Cell Intrinsic Effects - Calise, Justine; Marquez Renteria, Susana; Gregersen, Peter K.; Diamond, Betty (Frontiers in immunology, 2018)
Interferon regulatory factor 5 (IRF5) is widely recognized as a risk locus for systemic lupus erythematosus (SLE). Risk gene and IRF5 activation is triggered through toll-like receptor signaling. In myeloid cells, this leads to production of type I interferon and inflammatory cytokines, with enhanced production in cells of individuals harboring IRF5 risk alleles. Mouse models have also demonstrated the importance of IRF5 in B cell function, particularly plasma cell differentiation and isotype switching. Here, we evaluated the major SLE risk haplotype of IRF5 on the functional attributes of freshly isolated B cells from human subjects who do not have evidence of SLE or other forms of autoimmunity. We took this approach to avoid the complications of studying genotype-phenotype relationships in B cells that have been chronically exposed to an inflammatory disease environment before isolation. We focused on B cell endophenotypes that included gene expression, antibody secretion, class switching, and apoptotic susceptibility. We performed IRF5 overexpression studies, genetic reporter assays and electro-mobility shift assays on B and myeloid cell lines. Somewhat surprisingly, the results of our analyses indicate that IRF5 risk genotypes do not have a B cell intrinsic effect on these B cell functions. By contrast, we confirmed that the IRF5 risk and non-risk haplotypes exert differential effects in myeloid cells, including an increased susceptibility to apoptosis conferred by the risk haplotype. We also demonstrated an increased binding of the transcription factor specificity protein 1 to an insertion/deletion present in the risk haplotype. Our findings raise the specter that genetic risk alleles can have complex and unexpected lineage-specific effects, and these must be carefully considered when guiding or developing therapies based on understanding disease risk haplotypes.